The Characteristics and Biological Activities of Niosome-Entrapped Salicylic Acid-Contained Oleoresin from Dipterocarpus alatus for Skin Product Applications - Nattawadee Kanpipit; Suthasinee Thapphasaraphong; Srisan Phupaboon; Ploenthip Puthongking (Advances in Pharmacological and Pharmaceutical Sciences)
Salicylic acid (SA) is widely renowned for its efficacy as a beneficial ingredient for skincare, especially for acne and uneven skin texture. The salicylic acid (SA) niosome formulation combined with the essential component of oleoresin from Dipterocarpus alatus Roxb. ex G. Don or Yang-Na (ODA) was developed and investigated for its physical characteristics, biological effects, and stability. The findings demonstrated that SA combined with ODA in the niosome formulation F4 enhanced the entrapment efficiency of SA, as well as the physical properties and stability of the formulation. Furthermore, the release pattern of this combined formulation indicated sustained release of SA. The permeation of SA was higher in the presence of ODA compared to SA-niosome formulations without ODA. Moreover, this F4 could downregulate the secretion of iNOS, COX-2, and TNF-α including anti-Propionibacterium acnes activities. Consequently, the incorporation of ODA into the niosome formulation has the potential to improve the entrapment efficiency of SA, facilitating controlled release and enhancing permeation, nitric oxide inhibition capabilities, and anti-P. acnes activity. Therefore, F4 has the potential to be developed as a topical product for the combined treatment of inflammation and P. acnes-associated conditions in the future.